Proceedings of the Principles and Practices of Programming on the Java Platform 2015
DOI: 10.1145/2807426.2807436
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Interoperation between Generics Translations

Abstract: Generics on the Java platform are compiled using the erasure transformation, which only supports by-reference values. This causes slowdowns when generics operate on primitive types, such as integers, as they have to be transformed into reference-based objects.Project Valhalla is an effort to remedy this problem by specializing classes at load-time so they can efficiently handle primitive values. In its current early prototype 1 , the Valhalla compilation scheme limits the interaction between specialized and er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…Wider use of miniboxing suggested that similar specialization techniques can harm performance if specialized code is called frequently from generic code and vice versa (Ureche et al 2015). Consider the following example.…”
Section: Specialization Techniquesmentioning
confidence: 99%
“…Wider use of miniboxing suggested that similar specialization techniques can harm performance if specialized code is called frequently from generic code and vice versa (Ureche et al 2015). Consider the following example.…”
Section: Specialization Techniquesmentioning
confidence: 99%
“…The miniboxing implementation also provides warnings ("performance advisories") to notify the programmer about the code locations where boxing and unboxing operations are inserted and to suggest annotations that would eliminate them (Ureche et al 2015). However, the fundamental problems remain.…”
Section: Application To Specializationmentioning
confidence: 99%
“…In contrast, the value a in the generic method bar1 will already be boxed before bar1 is called, so it will not have to be boxed again in every iteration of the loop. The miniboxing implementation tries to help users to solve this problem by providing comprehensive warnings that suggest possible changes to the code (Ureche et al 2015).…”
Section: Specialization Techniquesmentioning
confidence: 99%
“…The adrt scoped transformation is a conceptual generalization of a mechanism motivated by library transformation scenarios. In particular, the resulting data representation transformation is used in conjunction with the miniboxing transformation [6,46] functions and tuples by custom, optimized versions adequate for miniboxed code [48]. The scope of this data representation transformation is miniboxing-transformed code.…”
Section: Adrt In Realistic Librariesmentioning
confidence: 99%